Development and personal self-realization of mining workers in a mining company with quality management Huancayo – Diciembre 2016 - Nuñez Inga, Linda (2017)
The article Development and Personal Self - Realization of the Mining Workers of Socavón in a Mining Company with a Quality Management (Case Mining Milpo - Cerro Lindo Mine), based on the research carried out by the author, the psychosocial well - being of the workers of the Mining Center Milpo-Chincha Alta-2015¨, assumes two dimensions of the psychosocial well-being of the human being, and the Purpose of Life and Personal Growth, in relation to a company that implements a Quality Management, with the obtained results proving that a tendency is given Dominant negative in relation to these dimensions and that it is necessary to deepen with scientific criteria the situation of the psychosocial welfare of the mining workers, as is the case of the object of study.